A Conceptual Framework for Big Data Analytics Adoption Towards the Success of Industry 4.0 - Muhammad, Nur Khairiah; Osman, Nor Hasni; Salleh, Nurul Azita (2020)
The rise of Big Data has inspired business organizations to venture into Big Data analytics, however academic research and empirical evidence about the business value remains scarce. This paper attempts to evaluate the readiness of Malaysia companies in taking advantage of Big Data adoption. Initial insights highlighted the definition and challenges surrounding Big Data. The research finds a great interest about Big Data Analytics (BDA) solutions that fuel with sound decision making and influence organizations into growth mindset. Big Data provides various advantages to organization that would seriously consider all its perspectives alongside its lifecycle in the pre-adoption or implementation phase. The research attempts to outline the different aspects of Big Data as a management practices to leverage the values of Big Data adoption as part of Industry 4.0 vision in future organizations. This is of great interest to researchers, professionals, and policy makers